Improved approximation of SISO and MIMO continuous interval systems. (14th September 2021) - Singh, V.P.; Dewangan, P.D.; Sinha, S.L.
Recently, some engineering systems are modelled as interval systems. In this investigation, an improved approximation method is first presented for reducing the order of single-input-single-output (SISO) continuous interval systems and then the same method is extended for reducing the order of multi-input-multi-output (MIMO) continuous interval systems utilising multi-point Padé approximation. In contrast to traditional Padé approximants, multi-points are used for matching the response of higher order system to that of its model in case of multi-point Padé approximation. Matching around multi-points improves the overall quality of approximation. The multi-point Padé approximation is proposed for SISO system firstly. A test case for SISO system is considered to illustrate the efficacy of proposed method. Secondly, multi-point Padé approximation is extended for reducing the order of MIMO continuous interval systems. The proposed method is also investigated for one MIMO test case. From the results obtained for SISO and MIMO test cases, it is observed that multi-point Padé approximation is able to provide better approximants.